Football and the video assistant referee: A grounded theory approach - Pashaie, S.; Dickson, G.; Abdavi, F.; Azarin, Y. B.; Golmohammadi, H.; Zheng, J.; Habibpour, R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2026)
Few studies have examined the impact of technological officiating aids on football. The purpose of this study is to design a comprehensive model examining the use of video assistant referee (VAR) technology in football. Based on interviews with eminent sports experts, this study explores the use of VAR technology in football and provides a paradigm model. Data analysis was based on the continuous comparison method during three stages of open, axial and selective coding. The findings point to the ability of a referee to make an informed decision regarding an incident during a match and trends suggest continuing adoption of new technologies in decision support systems. In the model, causal conditions (e.g. rules and regulations, innovation in football) attract attention to the axial phenomenon (i.e. application of VAR technology to football) and strategies for its use (e.g. Total Quality Management, justice, increasing referee supervision) given the interfering factors (e.g. fair play, competition) and existing contexts (e.g. control of anti-football behaviours, referee performance, information technology, IT, control of violence and aggression), which create consequences (i.e. process weakness, slowing down the game, passion killing, increasing the quality of the referee`s decision, increasing referee confidence, economical, increasing decision-making accuracy). Therefore, given the contextual conditions and the intervening factors, implementing VAR technology should improve the quality of football competitions. The research concludes that VAR has the potential to enhance the quality of football competitions but also acknowledges the need to address its negative impacts and ensure sustainable development.